Is there a survival benefit from adjuvant chemotherapy for patients with liver oligometastases from colorectal cancer after curative resection?. Issue 1 (29th May 2018) - Pan, Zhizhong; Peng, Jianhong; Lin, Junzhong; Chen, Gong; Wu, Xiaojun; Lu, Zhenhai; Deng, Yuxiang; Zhao, Yujie; Sui, Qiaoqi; Wan, Desen
Abstract: Background: Although colorectal oligometastases to the liver can potentially be cured with aggressive local ablation, the efficacy of adjuvant chemotherapy (ACT) for such metastasis remains unclear. The present study explored the effects of ACT on patients with colorectal liver oligometastases (CLO) after curative resections and aimed to identify patients who could benefit from ACT. Methods: We retrospectively analyzed 264 eligible patients with CLO who underwent curative resection between September 1999 and June 2015. Recurrence‐free survival (RFS) and overall survival (OS) were analyzed using the Kaplan–Meier method and log‐rank test; prognostic factors were a by Cox regression modeling. Results: Among 264 patients, 200 (75.8%) patients received ACT and 64 (24.2%) did not receive ACT. These two groups did not significantly differ in clinicopathologic characteristics, and had comparable 3‐year OS and RFS rates (RFS: 42.1% vs. 45.7%, P = 0.588; OS: 69.7% vs. 62.7%, P = 0.446) over a median follow‐up duration of 35.5 months, irrespective of preoperative chemotherapy. ACT markedly improved 3‐year OS in high‐risk patients with Memorial Sloan‐Kettering Cancer Center clinical risk scores (MSKCC‐CRS) of 3–5 (68.2% vs. 33.8%, P = 0.015), but presented no additional benefit in patients with MSKCC‐CRS of 0–2 (72.2% vs. 78.6%, P = 0.834). In multivariate analysis, ACT was independently associated with improved OS in patients with MSKCC‐CRS of 3–5. Conclusions: ACT might offer a prognostic benefit in high‐risk patients with CLOs after curative liver resection, but not in low‐risk patients. Therefore, patients' risk status should be determined before ACT administration to optimize postoperative therapeutic strategies.